Causes of Saints (The catholic historical review, 2018)
A list of the saints declared by Pope Francis to be canonized on October 14, 2018 is presented, along with the list of venerable servants of God who were declared in light of their heroic virtue, and a list of a group of three priests and five women religious recognized as venerable servants of God.